Deciphering the Therapeutic, Larvicidal, and Chemical Pollutant Degrading Properties of Leaves-mediated Silver Nanoparticles Obtained from Alpinia purpurata - Manikandan Vani Raju; Meenakshi Kaniyur Chandrasekaran; Meenakshi Sundari Rajendran; Gopalakrishnan Velliyur Kanniappan; Rathi Muthaiyan Ahalliya; Guru Kumar Dugganaboyana; Mikhlid H Almutairi; Bader O. Almutairi; Ameer Khusro; Ponnuswamy Vijayaraghavan (BioResources, 2024)
The aim of the study was to synthesize silver nanoparticles (AgNPs) from Alpinia purpurata leaves and evaluate their cytotoxic, antimicrobial, antibiofilm, dye degradation, and larvicidal potentials. The synthesized AgNPs were characterized using ultraviolet-visible spectroscopy, Fourier transform infrared, and high-resolution transmission electron microscopy, which confirmed AgNPs synthesis and revealed nanoparticle size (10 to 30 nm) and the presence of silver. Cytotoxicity tests showed IC50 values of 4.59 ± 0.6 µg/mL in A549 cells and 3.48 ± 0.4 µg/mL in PA1 cells, inducing apoptosis and DNA fragmentation. Flow cytometry revealed cell cycle arrest at G0-G1 phase. AgNPs exhibited significant antimicrobial activity, with maximum inhibition zones against K. pneumoniae (23 ± 2 mm) and F. oxysporum (17 ± 2 mm), and minimum inhibitory concentration (MIC) values ranging from 12.5 ± 0.25 to 75 ± 2.5 µg/mL. They also reduced bacterial and fungal biomass and showed antibiofilm effects. Photocatalytic activity degraded methylene blue dye by 88.4 ± 1.4% in 60 minutes. Larvicidal activity resulted in 100% mortality of A. aegypti larvae after 48 hours exposure to AgNPs (10 mg/L), additionally reducing chemical oxygen demand (55.1 ± 2.1% to 63.8 ± 1.5%) and microbial load in wastewater (2.5 to 10 ppm).